PENGARUH LINGKUNGAN KERJA, MOTIVASI KERJA, DAN STRES KERJA TERHADAP KINERJA KARYAWAN PT NIVEN BINA BENING - Kristian, David; Jontro Simanjuntak (SCIENTIA JOURNAL, 2022)
Human resources (HR) in an organization should be a worry to further develop performance that can assist the organization with accomplishing its objectives. This study aims to determine the effect of work environment, work motivation, and work stress on employees either partially or simultaneously at PT Niven Bina Bening in Batam City. The population studied in this study were employees of PT Niven Bina Bening in Batam City, the sample in this study amounted to 100 respondents. The method of this research is to use a saturated sample technique and is carried out by a questionnaire method. The data analysis technique used is multiple linear regression analysis, t test and F test. The method used is a quantitative method with causality research. While the data analysis method used in this research is multiple linear regression analysis method with SPSS tools. The results of this study indicate that the work environment and motivation on employee performance simultaneously have a positive and significant effect on employee performance, where the value of tcount is 2.441 (positive value) > ttable 1.98498 and sig from the work environment is 0.016 which is below 0.05 and the value of the motivational variable is tcount 5.272 (positive value) > ttable 1.98498 and sig 0.000 which value is <0.05, while work stress does not simultaneously affect employee performance because from the test the value of tcount is -0.760 (negative value) < ttable 1.98498 and sig 0.449 whose value is > from 0.05. And the value of the F test with a value of Fcount 12.759 and Ftable > 2.698 so that it can be concluded that Ho is rejected, Ha is accepted or the variables of work environment, work motivation and work stress have a simultaneous effect on employee performance.